Vaccine Adjuvants Induce Formation of Intraperitoneal Extracellular Traps in Flounder (Paralichthys olivaceus) - Li, Qian; Chi, Heng; Shi, Xueyan; Gan, Qiujie; Dalmo, Roy Ambli; Sun, Yuan-yuan; Tang, Xiaoqian; Xing, Jing; Sheng, Xiuzhen; Zhan, Wenbin (Frontiers in Cellular and Infection Microbiology, 2022)
Adjuvants are used to increase the strength, quality, and duration of the immune response of vaccines. Neutrophils are the first immune cells that arrive at the injection site and can release DNA fibers together with granular proteins, so-called neutrophil extracellular traps (NETs), to entrap microbes in a sticky matrix of extracellular chromatin and microbicidal agents. Similar extracellular structures were also released by macrophages, mast cells, and eosinophils and are now generalized as “ETs.” Here we demonstrated that Alum adjuvant stimulation led to peritoneal cells swarming and ET release in vitro. Moreover, compared to antigen stimulation alone, ET release was significantly increased after stimulation with antigen-mixed adjuvants and in a time- and dose-dependent manner. In vivo, we were able to monitor and quantify the continuous changes of the ET release in the same fish by using the small animal in vivo imaging instrument at different times during the early stages after intraperitoneal immunization. The results showed that the fluorescence signal of ETs in the peritoneum increased from 0 to 12 h after injection and then gradually decreased. The fluorescence signals came from extracellular DNA fibers, which are sensitive to DNase I and confirmed by microscopy of peritoneal fluid ex vivo. In summary, this study introduced a new method for detecting ETs in the peritoneum of fish in vivo and indicated that ET formation is involved in the immune response at the early stage after intraperitoneal immunization to vaccines.